Assessment of the quality of life of breast cancer patients after one year of treatment - Tu, Hoang Ngoc; Quan, Le Quang; Tien, Nguyen Thi Kim; Dung, Ho Xuan (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
ABSTRACT Introduction: Breast cancer is the most commonly diagnosed malignancy and the leading cause of death among women worldwide. The incidence of breast cancer is on the rise in developing countries. Breast cancer patients not only experience physical pain from treatment but may also face mental crises, impaired social function, and impaired quality of life. However, there are not many studies on the quality of life (QoL) of post - treatment breast cancer patients. Therefore, we carried out the study “assessment the quality of life of breast cancer patients after one year of treatment” with aims to evaluate the quality of life of breast cancer patients after one year of treatment using the scales EQ-5D-5L and QLQ-BR23 and to find out related factors to the quality of life of these subjects. Methods: A cross - sectional study was conducted on 100 breast cancer patients after one year of treatment at the Hue University of Medicine and Pharmacy Hospital to examine the quality of life using the scales EQ-5D-5L and QLQ-BR23 and to detect the associated factors. Results: The mean quality of life score of breast cancer patients after one year of treatment on the EQ- 5D-5L scale was 0.6436 ± 0.2098. By QLQ-BR23, the quality of life score on function was 74.75 ± 20.78 while the score on symptoms was 28.80 ± 12.79. The quality of life from both scales was found to be statistically significant related to social work participation, self - reported health, risk of depression, anxiety, and stress. Conclusions: The quality of life of breast cancer patients in the study was at a moderate level. This suggests more supports to be done continuously after long - term post - diagnosing especially psychological and social aspects for these subjects.